KEWENANGAN PEMERINTAH PROVINSI SEBAGAI BADAN PUBLIK DALAM MENYAJIKAN PENGELOLAAN APBD T.A. 2023 DI DKI JAKARTA: The Authority of the Provincial Government as a Public Entity in Presenting the Management of the 2023 Regional Budget in DKI Jakarta - Nurhalisa, Siti; Purnomowati, Reni Dwi (Faculty of Law, Universitas Trisakti, 2025)
Transparency in all sectors of government work programs is a very important element because it is directly related to public trust. In budget matters, where the main key must prioritize transparency, the focus of the government, in this case, the provincial government of DKI Jakarta as a Public Agency, is to present the management of the 2023 fiscal year budget (APBD) as public information. However, in reality, violations of transparency are still found within the DKI Jakarta provincial government agencies. This raises the question: what is the authority of the DKI Jakarta Provincial Government as a Public Agency in presenting the management of the 2023 fiscal year budget as public information? This research uses a normative type of study with secondary data. The nature of the research is descriptive, and conclusions are drawn deductively. From the research results, the form of authority of the DKI Jakarta provincial government in presenting the management of the 2023 fiscal year budget as public information is through a user-friendly application called the Smart Planning & Budgeting System (SPB). This platform contains information related to the budget in DKI Jakarta, allowing the public to directly participate in supervising the provincial government's budget management.